Use and Perception of Generative AI in Higher Education: Insights from the ERASMUS+ Project 'Teaching and Learning with Artificial Intelligence' (TaLAI) - Rudra, Susmita; Weber, Peter; Tillmanns, Tanja; Salomao Filho, Alfredo; Wiersma, Emma; Dawitz, Julia; Dudenaite, Dovile; Reynolds, Sally (Proceedings of the 17th International Conference on Computer Supported Education - Volume 2: CSEDU,, 2025)
The integration of Generative Artificial Intelligence (GenAI) in higher education offers transformative opportunities alongside significant challenges for both educators and students. This study, part of the ERASMUS+ project Teaching and Learning with Artificial Intelligence (TaLAI), aims to explore the familiarity, usage patterns, and perceptions of GenAI in academic settings. A survey of 152 students (mainly from Germany, Belgium, and the Netherlands) and 118 educators (81 professors, 37 trainers) reveals widespread GenAI use, with ChatGPT being the most common tool. Findings indicate both enthusiasm for GenAI’s potential benefits and concerns regarding ethical implications, academic integrity, and its impact on learning processes. While students and educators recognize GenAI’s ability to enhance learning and productivity, uncertainties persist regarding assessment practices and its potential short and long-term effects on various aspect such as decision making, creativity, and mem ory performance. The study also highlights gaps in institutional support and policy, emphasizing the need for clearer communication to ensure responsible AI adoption. This paper contributes to the ongoing discussions on GenAI in higher education and is aimed at educators, policymakers, and researchers concerned with its responsible use. By addressing students’ and educators' both perspectives and concerns, institutions and policymakers can develop well-informed strategies and guidelines that promote responsible and effective use of GenAI, ultimately enhancing the overall teaching and learning experience in academic environment
Keywords: Generative AI; Higher Education; Perception; Survey Results